Assessing primary versus secondary features in two pegmatite swarms with implications for the nature of pegmatitic systems - Pfister, Jérémie Damien (Laurentian University of Sudbury, 2023)
Understanding the processes behind the formation and evolution of pegmatites, which host globally significant resources of strategic metals (e.g., Li, Ta, Nb, Sn, Cs, Rb, Y, REE) critical to the global renewable energy transition, is paramount for their exploration and exploitation. This study investigates the nature, origin and evolution of two distinct pegmatite swarms (i.e., the LCT-type Little Nahanni Pegmatite Group, NWT, Canada, and the NYF-type Highway 69 Pegmatite Group, Ontario, Canada) in order to address several unresolved aspects of pegmatite genesis, such as the origin of pegmatite-forming melts (i.e., anatexis versus fractional crystallization), nature of various pegmatitic textures (i.e., primary versus secondary), metasomatism and re-mobilization of rare-metal mineralization, and influence of the host rocks on pegmatites (i.e., open- versus closed systems). This study integrates various aspects of field observations that include detailed mapping, field and petrographic observations (transmitted light, BSE, SEM-CL), bulk whole-rock and trace-elements geochemistry (ICP-AES, ICP-MS), in situ mineral analysis (SEM-EDS), in situ trace-elements analysis (LA-ICP-MS), bulk and in situ stable isotopes (O, H) geochemistry (DI-IRMS, SIMS), and in situ U-Pb geochronology (LA-ICP-MS). The principal findings suggest that: (1) both anatexis and fractional crystallization of a parental melt are viable processes of pegmatite formation; (2) most macroscopic pegmatitic textures are primary and are generally preserved during sub-solidus evolution of pegmatites; (3) late-stage, fine-grained albitic and micaceous units associated with significant rare-metal mineralization are secondary; (4) secondary micro-features related to coupled dissolution-precipitation processes in pegmatites are profuse, despite being rarely reported, and are frequently associated with accessory rare-metal mineralization; and (5) pegmatites evolve as partially open systems during both magmatic and metasomatic stages with influence from the ...